2021
DOI: 10.1111/bcp.15107
|View full text |Cite
|
Sign up to set email alerts
|

Implementing prescribing safety indicators in prisons: A mixed methods study

Abstract: Aims: To examine the prevalence of potentially hazardous prescribing in the prison setting using prescribing safety indicators (PSIs) and explore their implementation and use in practice.Methods: PSIs were identified and reviewed by the project team following a literature review and a nominal group discussion. Pharmacists at 2 prison sites deployed the PSIs using search protocols within their electronic health record. Prevalence rates and 95% confidence intervals (CIs) were generated for each indicator.Semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The 48 included studies which reported at least one opioid-related prescribing indicator (2, 9, 2469) were published during the period 2010-2019 (n=24)(13, 27, 28, 3033, 35, 3739, 41, 43, 45, 46, 49, 50, 54, 55, 57, 60, 63, 65, 66) followed by 2000-2009 (n=13) (9, 24, 29, 34, 42, 44, 48, 56, 58, 59, 62, 67, 68) and 2020-2022 (n=10) (2, 25, 26, 36, 40, 5153, 61, 69) and only one published in 1990-1999 (47) (Table 2). .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 48 included studies which reported at least one opioid-related prescribing indicator (2, 9, 2469) were published during the period 2010-2019 (n=24)(13, 27, 28, 3033, 35, 3739, 41, 43, 45, 46, 49, 50, 54, 55, 57, 60, 63, 65, 66) followed by 2000-2009 (n=13) (9, 24, 29, 34, 42, 44, 48, 56, 58, 59, 62, 67, 68) and 2020-2022 (n=10) (2, 25, 26, 36, 40, 5153, 61, 69) and only one published in 1990-1999 (47) (Table 2). .…”
Section: Resultsmentioning
confidence: 99%
“…The data of included studies were extracted by two reviewers (NS, WK) using an electronic data collection form and double-checked by two reviewers (NB, LCC). Three major categories of data were extracted from the literature, including (1) literature information: title, leading author, country, and year; (2) methodology: study design, setting, targeted population, indicators sources, and validation methods; and (3) opioid-related prescribe indicators: total number of indicators, opioids name of the medication, duration of medication, disease condition, concomitant medication, risk of the prescribing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed-methods study from 2021, involving synthesis of prescribing safety indicators, a literature review and nominal group discussion at two English prisons identified similar issues. 28 Notably, prescribing practices that could cause harm were clustered around several high-risk medications, including selective serotonin re-uptake inhibitors and anti-psychotics, which echoes the medication classes described in reports included in our study. Building on this, we shed light on issues involving poor medication access, including delays in receiving these medications.…”
Section: Medicationmentioning
confidence: 99%
“…This study therefore aimed to characterise and understand the processes and challenges to prescribing in prisons, explore the causes and impact of these challenges, and identify potential approaches to improve prescribing safety in prisons. Specifically, focus groups were designed to capture harms, as part of wider work to develop indicators of potentially hazardous prescribing (reported here [39]), and interviews (where in depth discussion of risks and benefits) aimed to identify areas of good practice. Prescribing safety indicators describe statements of potentially hazardous prescribing practices that may place patients at risk of harm, and have been utilised previously as part of a pharmacist-led intervention successfully implemented in general (or community) practice and secondary care [40].…”
Section: Introductionmentioning
confidence: 99%